The role of trust in mediation the effect of perception of ease of use and perception of usefulness on intention to re-using the mobile banking service - Prayudi, I Gede; Sukaatmadja, I Putu Gde; Yasa, Ni Nyoman Kerti; Giantari, I Gst Ayu Kt. (International research journal of management, IT and social sciences, 2022)
The purpose of this study was to examine and explain the role of trust in mediating the effect of perceived ease of use and perceived usefulness on the intention to reuse mobile banking on the BNI Mobile Banking application. This research is categorized as an associative quantitative research conducted in Denpasar City. Data consists of 160 samples, collected by distributing questionnaires containing open and closed questions and statements that have been tested for validity and reliability. The analysis technique used is the Structural Equation Model (SEM) using an analysis tool in the form of SmartPLS 3.0 software. The results of this study indicate that perceived ease of use and perceived usefulness have a positive and significant effect on trust and intention to reuse, and trust has a positive and significant effect on intention to reuse as well as partially mediate the relationship between perceived ease of use and perceived usefulness with intention to reuse to the BNI Mobile Banking application in Denpasar City.